The Longitudinal Role of Self-Concept Clarity and Best Friend Delinquency in Adolescent Delinquent Behavior - Levey EKV; Garandeau CF; Meeus W; Branje S (SPRINGER/PLENUM PUBLISHERS, 2022)
Adolescence tends to be characterized by a temporary peak in delinquent behavior, and friends in particular play a key role in the initiation and the development of delinquency. However, adolescents differ in their susceptibility to friends' influence on delinquency. Especially adolescents who are less certain about who they are might show more delinquent behavior, and might be more susceptible to their friends' behaviors, as friends are also crucial for adolescents' identity formation. In addition to examining the main effects of best friend's delinquency and self-concept clarity on the development of adolescents' delinquency, the current study scrutinized whether self-concept clarity moderated the longitudinal association between adolescents' and their best friends' self-reported delinquent behavior. The current study examined whether best friend delinquency and adolescent self-concept clarity were related to the development of adolescents' delinquency, and whether self-concept clarity moderated the relation between adolescent and best friend delinquency. Dutch adolescents (N=497, M-age Wave 1=13 years, 287 boys) and their best friends participated across six annual waves. Both adolescents and best friends reported on their delinquency and adolescents reported on their self-concept clarity. Adolescent delinquency linearly declined, and although adolescents' and best friends' delinquency levels were related, changes in delinquency of adolescents and best friends were not. Adolescents low on self-concept clarity reported higher levels of delinquency. Self-concept clarity also moderated the relation between adolescent and best friend delinquency levels, with stronger relations observed for adolescents with lower self-concept clarity. Future research should examine the protective role of self-concept clarity not only against delinquent behavior, but also against susceptibility to peer influence.